2019
DOI: 10.1186/s40364-019-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring disease activity and predicting response to intravenous immunoglobulin in chronic inflammatory demyelinating polyneuropathy

Abstract: Chronic inflammatory demyelinating polyneuropathy (CIDP) is characterised by significant clinical heterogeneity and as such reliable biomarkers are required to measure disease activity and assess treatment response. Recent advances in our understanding of disease pathogenesis and the discovery of novel serum-based, electrophysiologic and imaging biomarkers allow clinicians to make more informed decisions regarding individualised treatment regimes.As a chronic immune-mediated process typified by relapse followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…As previous studies have shown, NCS results, including possible axonal changes (no or very low amplitude), do not reflect neither the disease severity nor response to treatment (27,28). Features of the inflammation of nerve roots seen in MRI are observed more often in adults, ∼60%, than in children, 38% (3).…”
Section: Discussionmentioning
confidence: 98%
“…As previous studies have shown, NCS results, including possible axonal changes (no or very low amplitude), do not reflect neither the disease severity nor response to treatment (27,28). Features of the inflammation of nerve roots seen in MRI are observed more often in adults, ∼60%, than in children, 38% (3).…”
Section: Discussionmentioning
confidence: 98%
“… 6–8 To this date, however, reliable prognostic serum-based biomarkers applicable to the general population of CIDP patients are not yet available. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Second, the ethnical differences and genetic backgrounds between Italy and China may represent reasons for the different rates of disease progression. Finally, several studies have shown that different treatment initiation times and treatment regimens may also lead to different results [26][27][28] . The uneven distribution of medical resources and limited therapeutic levels in China lead to the late start of treatment for patients, and most patients are treated with hormones; only a few patients have received a single course of IVIg (intravenous immunoglobulin).…”
Section: Discussionmentioning
confidence: 99%